The allyn & bacon guide to writing - Ramage, John D. (Simon and Schuster, 1997)
The book's content presents instruction in rhetoric and composition, a flexible series of comprehensive writing exercises, numerous examples of writing, and thorough instructions for research and editing. Key themes: Emphasize writing as a process of inquiry, problem-solving, and problem-solving. It provides balanced coverage of academic writing and personal and narrative forms, and provides readers with a continuum to understand the difference between academic writing, thesis, "closed form" and individual articles, "open form". The accessible readings throughout clearly illustrate the principles of rhetoric and present a balance between professional and student writers.